Women, Islam and education in Iran
1 online resource (xiv, 162 pages).
Keywords: Drawing on the complexities and nuances in women's education in relation to the aftermath of the 1979 Iranian Revolution, this edited collection examines implications of religious-based policies on gender relations as well as the unanticipated outcomes of increasing participation of women in education. With a focus on the impact of the Islamic Republic's Islamicization endeavor on Iranian society, specifically gender relations and education, this volume offers insight into the paradox of increasing educational opportunities despite discriminatory laws and restrictions that have been imposed on women.